2020
DOI: 10.1111/hae.13988
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term analysis of the benefit of prophylaxis for adult patients with severe or moderate haemophilia A

Abstract: Introduction:Prophylaxis with factor VIII (FVIII) concentrates in children with haemophilia A (HA) is current standard of care. The benefit of prophylactic treatment for adult HA patients is not commonly accepted. Aim:To investigate the benefit of prophylaxis over on-demand treatment in adult and elderly patients with severe or non-severe HA in a real-life setting. Methods: Data from 163 patients comprising 1202 patient-years were evaluated for 7.5 (±5.3) years. The effects on the annual bleeding rate (ABR, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(148 reference statements)
0
10
0
Order By: Relevance
“…The initial literature search identified 236 unique articles, of which 91 were considered eligible for further screening (Figure 1). Twenty‐seven articles mentioned prophylaxis treatment for people with non‐severe HA, of which 15 were prospective 3,5,11–23 and 12 retrospective studies 9,24–34 (cohort studies, n = 10 3,11,13,24,26–28,32–34 ; observational studies, n = 11 12,15–18,22,23,25,29–31,34 ; cross‐sectional studies, n = 2, 5,9 other study types, n = 4 14,19–21 ). Most of the studies (19 out of 27) provided Level IV evidence (well‐designed case‐controlled or cohort studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial literature search identified 236 unique articles, of which 91 were considered eligible for further screening (Figure 1). Twenty‐seven articles mentioned prophylaxis treatment for people with non‐severe HA, of which 15 were prospective 3,5,11–23 and 12 retrospective studies 9,24–34 (cohort studies, n = 10 3,11,13,24,26–28,32–34 ; observational studies, n = 11 12,15–18,22,23,25,29–31,34 ; cross‐sectional studies, n = 2, 5,9 other study types, n = 4 14,19–21 ). Most of the studies (19 out of 27) provided Level IV evidence (well‐designed case‐controlled or cohort studies).…”
Section: Resultsmentioning
confidence: 99%
“…The initial literature search identified 236 unique articles, of which 91 were considered eligible for further screening (Figure 1 ). Twenty‐seven articles mentioned prophylaxis treatment for people with non‐severe HA, of which 15 were prospective 3 , 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 and 12 retrospective studies 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 (cohort studies, n = 10 3 , 11 , 13 , 24 , 26 , 27 , 28 , 32 , 33 , 34 ; observational studies, n = 11 12 , 15 , 16 , 17 , 18 , 22 , 23 , 25 , 29 , 30 , 31 , 34 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylaxis can vary in terms of the duration of treatment: short-term prophylaxis (1–3 months) and long-term prophylaxis (continuous treatment). Of the studies included, 2 studies reported short-term prophylaxis [ 37 , 43 ], whereas 14 studies reported long-term prophylaxis [ 7 , 17 , 22 – 24 , 28 , 31 , 34 36 , 38 , 39 , 41 , 49 ]. Long-term prophylaxis resulted in better outcomes than short-term prophylaxis and also showed the need for continuing treatment at adolescence and adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, factor prophylaxis helped people with hemophilia to move freely, with little fear of trauma, and favoured a better quality of life [4,5]. Different replacement therapy regimens are currently available, and patients with hemophilia A and B may receive either prophylaxis or on-demand treatment by using different types of clotting factor concentrates [6,7]. The opportunity of an efficient prophylaxis reduces the risk of bleedings and should also reduce patients' and caregivers' fear of the noxious consequences of physical activity.…”
Section: Introductionmentioning
confidence: 99%